Analisis Dampak Prokrastinasi Akademik terhadap Prestasi Mahasiswa Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya - Nasrul Hidayat; Siti Nuraliya; Anita Nuraisah; Wina Amelia; Syahrul Alamsyah (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Academic procrastination—the habitual tendency to postpone task completion—remains a prevalent challenge among university students, including those in Guidance and Counseling (GC) programs. Beyond its effects on academic outcomes, this behavior also carries significant psychological consequences, a matter of particular concern given that GC students are expected to develop robust self-regulation competencies as future professional counselors. The present study sought to examine in depth how academic procrastination shapes the academic performance of GC students at Universitas Muhammadiyah Tasikmalaya. A total of 16 active students from the 2023, 2024, and 2025 cohorts were recruited through purposive sampling. Employing a descriptive qualitative design, the study gathered data via structured in-depth interviews comprising 10 questions that addressed multiple dimensions of the procrastination experience. Interview transcripts were produced verbatim in digital form and subsequently subjected to thematic analysis through three sequential coding procedures: open, axial, and selective coding. The results indicate that procrastination exerts adverse effects across four principal domains: task quality (87.5% of participants rushed through assignments), academic grades (81.25% reported declining scores), mastery of course content (81.25% experienced diminished understanding), and psychological well-being (93.75% felt anxious as deadlines neared). To counter procrastination, students employed both personal strategies—such as constructing daily schedules and ranking tasks by priority—and peer-based strategies, notably collaborative study sessions. It is anticipated that these findings will inform the design of more systematically structured intervention programs within GC departments.